(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Public-privatepartnerships are an approach that has been used in provision of affordablehousing in the United States, as well as in a number of other countries, sincethe 1980s. In these partnerships, private developers, non-profit agencies, andin some cases religious agencies receive some funds or support from themunicipal, state, or federal government (or all three, in some cases) in order tobuild or renovate and manage affordable housing. This can be used both forrental housing and as a means of encouraging low-income home ownership. This isalso an approach that has been used in a number of other countries. However,the effectiveness of public-private partnerships in the management ofaffordable housing is not a matter of uncontroversial agreement, and in facthas been challenged by a number of different research studies. By focusingresearch on a single city that has used public-private partnerships in managingaffordable housing, the research proposed will attempt to identify specificissues within the public-private partnership and gauge its effectiveness inthis city.